PENGARUH DISIPLIN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR DESA DINAS GUMBRIH DI PEKUTATAN JEMBRANA - Ni Kadek Adilia Meliana Putri; Ida Bagus Made Widiadnya; Sapta Rini Widyawati (VALUES, 2022)
Good employee productivity will increase profits in office institutions and be able to influence the success of an institution to achieve a goal. In order to increase work productivity, the application of a disciplinary system in office institutions must be more applied and maintained, as well as work stress if it is not managed properly it will have a negative impact on employee productivity. The purpose of this study was to determine and analyze the effect of work discipline and work stress on employee work productivity at the Gumbrih Village Office in Pekutatan Jembrana. The population in this study included 46 employees at the Gumbrih Service Village Office in Pekutatan Jembrana. The sampling technique in this study is saturated sampling, where the sampling technique is when all members of the population are used as samples. In this study, the samples were employees at the Gumbrih Service Village Office from several divisions, with a total of 46 employees. Data analysis using multiple linear regression. The result of this research is that work discipline has a positive influence on work productivity. Work stress has a negative and significant effect on work productivity at the Gumbrih Village Office in Pekutatan Jembrana.